Transplantation with autologous bone marrow‐derived mesenchymal stem cells for alcoholic cirrhosis: Phase 2 trial. Issue 6 (30th July 2016) - Suk, Ki Tae; Yoon, Jung‐Hwan; Kim, Moon Young; Kim, Chang Wook; Kim, Ja Kyung; Park, Hana; Hwang, Seong Gyu; Kim, Dong Joon; Lee, Byung Seok; Lee, Sae Hwan; Kim, Hong Soo; Jang, Jae Young; et al.
Abstract : Bone marrow‐derived mesenchymal stem cell (BM‐MSC) transplantation has been suggested as an effective therapy for liver cirrhosis. The efficacy and safety of autologous BM‐MSC transplantation in the treatment of alcoholic cirrhosis were investigated. Seventy‐two patients with baseline biopsy‐proven alcoholic cirrhosis who had been alcohol‐abstinent for more than 6 months underwent a multicenter, randomized, open‐label, phase 2 trial. Patients were randomly assigned to three groups: one control group and two autologous BM‐MSC groups that underwent either one‐time or two‐time hepatic arterial injections of 5 × 10 7 BM‐MSCs 30 days after BM aspiration. A follow‐up biopsy was performed 6 months after enrollment, and adverse events were monitored for 12 months. The primary endpoint was improvement in fibrosis quantification based on picrosirius red staining. The secondary endpoints included liver function tests, Child‐Pugh score, and Model for End‐stage Liver Disease score. Outcomes were analyzed by per‐protocol analysis. In terms of fibrosis quantification (before versus after), the one‐time and two‐time BM‐MSC groups were associated with 25% (19.5 ± 9.5% versus 14.5 ± 7.1%) and 37% (21.1 ± 8.9% versus 13.2 ± 6.7%) reductions in the proportion of collagen, respectively ( P < 0.001). In the intergroup comparison, two‐time BM‐MSC transplantation in comparison with one‐time BM‐MSC transplantation was not associated with improved results in fibrosis quantification ( P > 0.05). The Child‐Pugh scores of both BM‐MSC groups (one‐time 7.6 ± 1.0 versus 6.3 ± 1.3 and two‐time 7.8 ± 1.2 versus 6.8 ± 1.6) were also significantly improved following BM‐MSC transplantation ( P < 0.05). The proportion of patients with adverse events did not differ among the three groups. Conclusion : Autologous BM‐MSC transplantation safely improved histologic fibrosis and liver function in patients with alcoholic cirrhosis. (Hepatology 2016;64:2185‐2197)